The relationship between total cholesterol and postpartum impaired glucose tolerance in women with gestational diabetes mellitus - Wang, Dongyu; Ding, Wenjing; Xu, Shuqia; Chen, Haitian; Liu, Bin; Wang, Zilian (Lipids in health and disease, 2020)
History of gestational diabetes mellitus (GDM) and serum lipid abnormalities were associated with postpartum impaired glucose tolerance. To investigate the association between concentration of total cholesterol (TC), at the time of GDM diagnosis, and risk of postpartum glucose intolerance. Women who were diagnosed GDM with a live singleton delivery between January 1, 2013 and December 31, 2017 were included. Women were grouped based on the TC quartiles at the time of GDM diagnosis and had an OGTT at 6-12 weeks after delivery. The relationship between TC and the risk of postpartum glucose intolerance was assessed by COX regression. A total of 845 women were in the final analysis. Higher TC quartile at diagnosis of GDM was associated with a decreased risk of postpartum glucose intolerance. Women in the highest TC quartile (>7.0 mmol L ) had approximately only half-risk of any postpartum glucose intolerance, compared with women in the lowest TC quartile (<5.5 mmol L ). The decreased concentration of TC, at the time of GDM diagnosis, was related to an increased risk of postpartum abnormal glucose regulation in GDM women. Therefore, because both excessively increased and decreased TC were associated with pregnancy and postpartum complications, the optimal concentration of maternal TC throughout pregnancy remained to be further researched.